Antidiabetic Function of Lactobacillus fermentum MF423-Fermented Rice Bran and Its Effect on Gut Microbiota Structure in Type 2 Diabetic Mice - Ai, Xiaojuan; Wu, Cuiling; Yin, Tingting; Zhur, Olena; Liu, Congling; Yan, Xiaotao; Yi, CuiPing; Liu, Dan; Xiao, Linhu; Li, Wenkai; Xie, Binbin; He, Hailun (Frontiers in Microbiology, 2021)
Rice bran is an industrial by-product, exerting several of bioactivities in spite of its limited bioavailability. In this study, rice bran was fermented with Lactobacillus fermentum MF423 (FLRB) had enhanced antidiabetic effect both in vitro and in vivo. FLRB could increase glucose consumption and decrease lipid accumulation in insulin resistant HepG2 cells. 8-week treatment of FLRB could significantly reduce the levels of blood glucose and lipid and elevate antioxidant activity in type 2 diabetic mellitus (T2DM) mice. H&E staining revealed alleviation overt lesions in liver of FLRB treatment mice. Moreover, high-throughput sequencing showed notable variation in composition of gut microbiota in FLRB-treated mice, especially for short-chain fatty acids (SCFAs)-producing bacteria such as Dubosiella and Lactobacillus. In conclusion, our results suggested that rice bran fermentation products can modulate the intestinal microbiota and improve T2DM-related biochemical abnormalities, so it can be applied as potential probiotics or dietary supplements.